Influence of cryogenic thermal treatment on mechanical properties of an Al–Cu–Mg alloy. Issue 4 (4th March 2018) - Araghchi, M.; Mansouri, H.; Vafaei, R.
ABSTRACT: In this study, a cryogenic thermal treatment is developed and its effects on mechanical properties and precipitates are investigated. Water-quenched samples were immersed in liquid nitrogen and reheated in hot oil at 180°C or boiling water for 5 min. Finally, the samples were artificially aged at 190°C for 12 h. The results indicated a notable increase of about 75 MPa in the ultimate tensile strength in comparison to T6 heat-treated alloy. TEM observations revealed that the S(S′) precipitates were fine and uniformly distributed in the microstructure due to reheating in hot oil and subsequent aging treatment.